Menggagas Ideal Keterlibatan Ormas Keagamaan dalam Mengelola Tambang (Sebuah Refleksi Teologis) - Baylon, Oktavianus; Jelatu, Fulgensius; Panjo, Saverinus; Syukur, Daniel Oktaviano; Dosom, Saverinus (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to initiate the ideal involvement of religious mass organizations in managing mines. The method used in this study is descriptive qualitative with a literature study approach. The author collects, reviews and explores various literature in the form of books, journals, articles, and magazines, then elaborates them with the topic of this study. The results of this study indicate that the involvement of religious mass organizations in managing mines is in a dilemma, namely on the one hand, this involvement can encourage an increase in economic value. However, on the other hand, this involvement actually undermines the entity of the mass organization itself as a moral pioneer. This is because mining activities carried out by religious mass organizations have the potential to damage the environment, considering that mining activities have so far been full of destructive impacts on ecological integrity. Coal mining activities, for example, often have destructive impacts on the environment such as water pollution, air pollution, damage to flora and fauna, and so on. This is certainly contrary to religious mass organizations which should be moral guardians and pioneers in preserving the environment. However, we certainly do not need to be too pessimistic about the involvement of religious mass organizations. What we need to demand is what pattern religious mass organizations should adopt in managing mines. This research attempts to propose the ideal involvement of religious mass organizations, namely managing mines based on moral values ​​as taught in religion.